Ecosociety : a historical study of ecological man - Hart, Robert A. De J. (Dehradun, 1984)
This book discusses the role of forests and tree crops in farming and offers detailed advise and information on various economic species, the use of their products for food and raw materials, planting techniques and suggestions and guidance for the layout and operation of schemes of Forest Farming. The book is intended to meet the need for a handy reference and working manual. It has been written simply, but it contains enough technical material to serve the purposes of agriculturists and foresters in all countries and conditions, and seeks to provide useful idance and practical instructions for extension workers: planners, government departments concerned with development and research and indeed all those interested in tree growing, whether they be laymen or professionals.
Keywords: Human ecology